Address Presenting the Fifth Annual Report - Black, Eugene R. (World Bank, Washington, DC, 2019)
Eugene R. Black, President of the International Bank for Reconstruction and Development, spoke about the war in Korea and the repercussions around the world. He discussed how much progress was being made in Europe in hammering out new patterns of production and trade to replace and improve prewar patterns that cannot be restored. He also said that with the cooperation of the members, Bank can aid, in creating confidence and the kind of economic environment which will encourage productive investment, both local and foreign, private and public. He examined some of the steps underdeveloped nations must take in order to effectively translate aid into concrete development.